The genus Neoheegeria with a new species from Iran exhibiting wing-dimorphism (Thysanoptera: Phlaeothripidae) - Minaei, Kambiz; Fekrat, Lida; Mound, Laurence (Zootaxa, 2018)
Neoheegeria astragali sp.n. is described as the first known member of this genus to exhibit wing-dimorphism. Collected on Astragalus sp. [Fabaceae] in Iran, it is also unique among Neoheegeria species in having the tube unusually short. Neoheegeria sinaitica is recorded from Iran for the first time, and an illustrated key is provided to the five species of Neoheegeria. Wing reduction among Haplothripini is discussed briefly, and it is concluded that most species of Neoheegeria are associated with species of Astragalus.